Motivational interview training improves self-efficacy of GP interns in vaccination consultations: A study using the Pro-VC-Be to measure vaccine confidence determinants. Issue 1 (31st December 2023) - Garrison, Amanda; Fressard, Lisa; Mitilian, Eva; Gosselin, Virginie; Berthiaume, Patrick; Casanova, Ludovic; Gagneur, Arnaud; Verger, Pierre
ABSTRACT: Immunization-specific motivational interviewing (MI), a patient-centered communication style used to encourage internal motivation for attitudinal and behavioral change, can provide healthcare professionals (HCPs) with the skills and practice required to respond to patients' doubts and concerns related to vaccines. We sought to assess the impact of an MI-training of General Practitioner (GP) interns on the psychosocial determinants of their vaccine confidence and behaviors. French GP interns participated in a virtual three-day MI-workshop in southeastern France. We used the validated Pro-VC-Be questionnaire – before and after the MI-workshop spanning over three months – to measure the evolution of these determinants. Scores before and after workshop trainings were compared in pairs. Participants' scores for commitment to vaccination (+10.5 ± 20.5, P = .001), perceived self-efficacy (+36.0 ± 25.8, P < .0001), openness to patients (+18.7 ± 17.0, P < .0001), and trust in authorities (+9.5 ± 17.2, P = 0.01) significantly increased after the training sessions, but not the score for confidence in vaccines (+1.5 ± 11.9, P = .14). The effect sizes of the four score improvements were moderate to large, with self-efficacy and openness to patients having the largest effect sizes ( P = .83 and 0.78, respectively). This study provides evidence that certain determinants of overall vaccine confidence in HCPs, reflected respectively in the openness to patients and self-efficacy scores of the Pro-VC-Be, improve after immunization MI-training workshops. Incorporating immunization-specific MI-training in the curriculum for HCPs could improve several necessary skills to improve HCP-patient relationships and be useful for vaccination and other healthcare services.